2005
DOI: 10.1142/s0252959905000233
|View full text |Cite
|
Sign up to set email alerts
|

Hua's Theorem With Five Almost Equal Prime Variables

Abstract: It is proved that each sufficiently large integer N ≡ 5 (mod24) can be written aswhere pj are primes. This result, which is obtained by an iterative method and a hybrid estimate for Dirichlet polynomial, improves the previous results in this direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Because the procedure is very similar to that used in [8], we only give the outline for the proof of Lemma 2. where δ χ = 1 or 0 according as the Dirichlet character χ is principal or not. Therefore, we can express the difference between S(α) and the expected major arc approximation to it as follows:…”
Section: The Major Arcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the procedure is very similar to that used in [8], we only give the outline for the proof of Lemma 2. where δ χ = 1 or 0 according as the Dirichlet character χ is principal or not. Therefore, we can express the difference between S(α) and the expected major arc approximation to it as follows:…”
Section: The Major Arcsmentioning
confidence: 99%
“…In the last integral, we take out |W (χ 1 , λ)| and |W (χ 2 , λ)|, and then use Cauchy's inequality, to get Thus our Lemma 2.1 follows form the following lemmas and an iterative approach (see [8] for a similar argument). The proofs of Lemmas 4.1-4.3 are standard.…”
Section: The Major Arcsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10]; Δ = 1 35 in ref. [11]. In this paper, we apply Theorem 1.1 in conjunction with the estimate in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Later Liu, Wooley, and Yu [10] showed that the exponent 2/5 can be improved to 3/8, and very recently, Harman and Kumchev [3] further reduced the exponent 3/8 to 5/14. There are also many other interesting approximations (see for example [1], [4], [9], [8], [13], [12] and their references).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%